Slice-Based Analog Design - Pablo Walker (IEEE, 2021)
Advances over the last decades in electronic design automation (EDA) for the design of digital integrated circuits (ICs), have led to the development of a robust set of tools and methodologies that automate almost all low-level phases of the digital design workflow. In contrast, analog IC design remains a mostly handmade, time-consuming and knowledge-intensive process. The amount of design iterations can be heavily cut down by the use of realistic value tables through the $g_{m}/I_{D}$ design technique; however, the process still remains time-consuming and error-prone, with an end result of limited applicability beyond the scope of the initial specifications. The slice-based design methodology, first introduced in this paper, is a new approach to analog IC design, suitable for implementation in EDA tools, that aims to reduce the amount of time and expertise required from the user. This methodology, inspired by the $g_{m}/I_{D}$ design technique, is based on the use of pre-designed circuit cells, which can be connected in parallel to scale important performance metrics. Although not limited to any particular fabrication process, the present paper explores the application of the proposed design methodology to CMOS technologies, and in the context of a particular target application: low-noise charge-sensitive amplifiers (CSA) used for instrumentation in particle physics experiments. The methodology was successfully applied and validated through the design, fabrication and testing of a CSA with configurable noise performance.